INDUSTRIAL GAS PURIFICATION USE OF BIOFILTERS - Irina Ramona PECINGINĂ (Fiabilitate şi Durabilitate)
Biological filtration systems is one of the current alternatives to remove residual volatile components of the air through biological means, without affecting the natural environment. Biofilters have a technology that uses microorganisms (bacteria) to treat emissions, in a secure economic and environmental quality. Biofilters consist of porous filters, which is distributed flue gas stream